Observed received signal level of RazakSAT S-band space to earth satellite transmission during nighttime - Basri, A.B.; Badron, Khairayu; Ismail, Ahmad Fadzil; Chanik, Abadi; Salim, Hamid; Ismail, Maszlan Yusof B. (PennWell Publishing Co., 2020)
In order to guarantee effective satellite service, the link budget for all conditions is important. From the path loss and attenuation statistics, the appropriate fade margin value calculated from the link budget for the specific desired quality of service (QoS) can be determined from outage statistics. In the case of a clear sky, the value depends significantly on the distance and conditions of the atmospheric layers and their composition. The signal loss depends only on distance and frequency in the absolute Free Space case. The results of distance in the investigation of determining the most suitable clear sky attenuation values at night time were explored in this report. The received signal levels of the Malaysian Low Earth Orbit (LEO) RazakSAT satellite were recorded according to the distances between the satellite and the Earth station. Using the S-band (Terminal Doppler Weather Radar) TDWR, the clear sky state where no water precipitation was reported. With established attenuation values, the satellite operator may determine whether it is appropriate to operate the power uplink and mitigation technique. The Malaysian National Space Agency (ANGKASA) provided the RazakSAT S-band (2,232 GHz) transmission signal data and received radar data from the Malaysian Department of Meteorology (MMD). As the distance varies along each flight route, the results provide understanding of observed path loss.